MELIHAT INTERAKSI TANYA JAWAB GURU MELALUI LENSA DIRI MURID DALAM PEMBELAJARAN MATEMATIKA - Muhammad Refiu Setiadi; Aisyah Aisyah (Universitas Batanghari Jambi, 2026)
This research aims to analyze and synthesize findings from various studies regarding teacher-student question-and-answer (Q&A) interactions within the context of mathematics education, specifically from the student's perspective. The methodology employed is a Systematic Literature Review (SLR), which involves reviewing relevant scientific articles published within a specific timeframe. The results of this review are expected to provide a comprehensive understanding of Q&A interaction patterns, the factors influencing them, and their subsequent impact on students' conceptual understanding and learning motivation